Globalization and regionalization : a view from Latin America and the Caribbean (2000)
Analyzes the tendencies of Latin America's and the Caribbean's recent integration to the world economy, mainly through trade and investment flows. Points out that the governments of the region are trying to integrate their economies to the world economy through bilateral, regional, hemispheric and multilateral relations.
Keywords: GLOBALIZATION